H54 Investigation of the effects of dopamine antagonist medication on cognition in huntington's disease. (September 2018) - Harris, Kate; Mason, Sarah L; Barker, Roger
Abstract : Whilst the diagnosis of Huntington's disease (HD) is reliant on the presence of motor disturbances, progressive cognitive impairments can precede overt motor features by up to 15 years (Paulsen, 2011) and often place the greatest burden on both HD patients and their families (Brandt and Butters, 1986). It has been hypothesised that there is an increase in DA transmission in early stages of HD as drugs that block DA receptors help alleviate the chorea (Cepeda, 2015). However, despite knowing that DA is critical for cognition in a healthy population, little is understood about the consequences of these early changes on cognition in HD. Importantly, it is not known this process if influenced by the DA antagonists used to treat motor features of HD. In this study we use the dataset from Enroll-HD, the world's largest observational study for Huntington's disease families, to assess the effects of dopamine antagonist medication on cognitive decline. Participants were grouped into those taking dopamine antagonist medication during the assessment period and a control group who were not taking DA medication but were matched for age, gender and disease stage using propensity score matching. Results showed that participants taking DA antagonists had a significantly greater annual decline in performance on the enrol cognitive task battery than those who were not on DA medication. Furthermore, a group of participants who came off dopamine antagonists during the assessment period did not differ from the control group in rate of cognitive decline during the period they were off the medication. Together these results suggest that dopamine antagonist medication may be detrimental to cognition, which has important implications for the clinical management of cognitive symptoms.